PUBLICISTIKADA AVTOR POZICIYASÍ - Tureshova, S.M. (SCIENCE and SOCIETY, 2025)
The article discusses the artistic skills and style of the author in journalistic works. Also, the essence and ideas of the topic were analyzed with the help of examples.